2021
DOI: 10.3390/ijerph18168448
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nutrients and Cardiovascular Risk Factors among Renal Transplant Recipients

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality in post-renal transplant recipients (RTRs). Adequate nutrient intake is a protective factor for CVD. We examined the associations of macronutrients and micronutrients with traditional and nontraditional CVD risk factors. Conducted from September 2016 to June 2018, this cross-sectional study included 106 RTRs aged ≥18 years with a functioning allograft. Dietary intake data from 3-day dietary records were collected. Nutrient intake adequacy was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In kidney transplant recipients in the USA for example, diet quality before transplantation, at 3 months and at 12 months post‐transplantation was low at all time points, and body weight increased during the same period 11 . Other studies of kidney transplant recipients' diets and body weight have reported similar findings 12,13 …”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In kidney transplant recipients in the USA for example, diet quality before transplantation, at 3 months and at 12 months post‐transplantation was low at all time points, and body weight increased during the same period 11 . Other studies of kidney transplant recipients' diets and body weight have reported similar findings 12,13 …”
Section: Introductionmentioning
confidence: 64%
“…11 Other studies of kidney transplant recipients' diets and body weight have reported similar findings. 12,13 Understanding the dietary habits of contemporary HTRs is essential for the conduct of effective dietary interventions to control weight and slow progression of other metabolic dysfunctions. We therefore aimed to assess dietary intake and diet quality, as well as to explore any association between diet quality and increase in post-transplant weight adjusted for height, termed body mass index (BMI), among adult HTRs in the Australian state of Queensland.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary food and nutrient intakes were calculated using nutrition analysis software (CofitPro version 1.0.0. Cofit HealthCare Inc., Taipei, Taiwan), according to Taiwan’s Ministry of Health and Welfare Food and Drug Administration database as described previously ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary data were collected through a 3-day dietary records (by self-reported and including 2 weekdays and 1 day on the weekend) and were assessed by a well-trained registered dietitian during regular followed clinics. Dietary food and nutrient intake were calculated according to Taiwan's Ministry of Health and Welfare Food and Drug Administration database and analyzed by using CofitPro nutrition analysis software (version 1.0.0, Cofit HealthCare, Taipei, Taiwan), as described previously 6 .…”
Section: Data Collection and Definitions Of Abnormal Lipid Profilesmentioning
confidence: 99%